Commentary on the Special Issue on Emotions in Reading, Learning, and Communication: A Big Step Forward, More Giant Leaps to Come. Issue 1 (7th February 2022) - Linnenbrink-Garcia, Lisa
ABSTRACT: The articles in this special issue take an important step in beginning to test the PET framework. Together, these articles illustrate the importance of considering individual differences in attitudes and prior knowledge as well as differences in task demands when investigating the role of emotions in shaping cognitive processing while reading texts. This commentary begins with a focus on the type of emotion being studied (e.g., preexisting emotions/mood, achievement emotions, epistemic emotions, topic emotions). Next, the function of emotions in cognitive processing and self-regulation is discussed, including a consideration of key findings from the articles in this special issue and additional considerations about the ways in which emotions may shape discourse processing. Finally, practical methodological matters relating to the investigation of emotions during discourse processing are considered. Throughout, contributions of the articles in this special issue are featured as well as suggestions for potential avenues for future research.